Role of TRPV4 in the Diagnosis and Treatment of Helicobacter pylori Infection in Children with Duodenal Ulcers. (4th January 2022) - Li, Chuanying; Cheng, Rong; Li, Lin; Chen, Miaomiao; Wu, Cheng
Abstract : Duodenal ulcer seriously affects the quality of life and life safety of children, but the pathogenesis of children with duodenal ulcer is still unclear. As an important second messenger in the body, Ca 2+ participates in the physiological and pathological processes of various diseases. Therefore, transient receptor potential vanilloid type 4 (TRPV4) as one of the channels that mediate Ca 2+ has attracted widespread attention in recent years. Here, we found that TRPV4 is highly expressed in children with duodenal ulcer and has good diagnostic value through specimens of children with duodenal ulcer, and animal experiments have proved that TRPV4 is also highly expressed in duodenal ulcer mice. In addition, TRPV4 can enhance intestinal permeability, thereby promoting further infiltration of inflammatory factors. In summary, these results indicate that TRPV4 is involved in the occurrence and development of duodenal ulcer. Therefore, this study provides the diagnostic and therapeutic value of TRPV4 in children with duodenal ulcer.